A novel stability indicating HPLC-method for simultaneous determination of atenolol and nifedipine in presence of atenolol pharmacopeoial impurities - Hisham Hashem & , Ibrahim Adel Ehab, Elhenawee Magda (Journal of Applied Pharmaceutical Science, 2015)
For the first time a simple, rapid and accurate stability indicating HPLC method is described for simultaneous quantification of atenolol and nifedipine in bulk powder and dosage form. Chromatographic separation was carried out on Intersil® reversed phase C18 column. Separation was done using gradient binary mobile phase of ACN and 50 mM NaClO4 in the ratio from 5: 95 to 50: 50 (v/v) within 8 minutes at flow rate of 1 mL/min and 30 °C. An UV detector was used at 230 nm for detection. The elution times of atenolol and nifedipine were found to be 6.05±0.02 and 14.50±0.04 minutes, respectively. The method was validated for system suitability, linearity, precision, limits of detection and quantitation, specificity, stability and robustness. Robustness study was done for small changes in temperature, flow rate, wavelength of detection and time to reach 50% of ACN in mobile phase. Stability tests were done through exposure of the analytes' solution for five different stress conditions. The limit of detection for both drugs was 0.04 µg mL-1. Limits of quantitation were found to be 0.12 µg mL-1 for atenolol and 0.11µg mL-1 for nifedipine. The recovery value of this method was 100.40±0.85% for atenolol and 100.30±1.10% for nifedipine.
Keywords: Atenolol and nifedipine, Quantitative HPLC-determination, Stability indicating, Pharmacopeoial impureties.